Prospectives for Applying of Nanocoatings on Instrumental Tools - Dubonosov, V. L.; Krichkovskaya, L. V.; Demyanenko, D. V.; Khrypunov, G. S.; Vodoriz, O. S. (My University, 2020)
The paper is devoted to development of technology and equipment for obtaining of protective reinforcing and heat-shielding thin-film coatings with controlled structure and their usage in production of tools with improved operating characteristics in technological engineering. Recent times much of attention has been paid to creating of wear-resistant hardening coatings and development of multilayer nanosized coatings. By changing the application parameters of such coatings, one can control the composition, particle size, morphology as well as thickness and number of individual layers. Due to this, they can be easily adapted to obtain optimal physical and mechanical properties. The most effective method for coating of cutting tools is ion-plasma vacuum-arc coating deposition (Arc-PVD) which is characterized by high deposition rate and high ionization degree of the vaporized material providing increased adhesion strength of a coating, and this is the main objective of the article.
Keywords: nanocoatings; cutting tools; methods of tool protection; ion-plasma coating